Manfaat Teknik Relaksasi Napas Dalam Untuk Menurunkan Kecemasan Pasien Pre Operasi General Anastesi - Hamarno, Rudi; Arif, Taufan; Oktavia, Devi Ayu; Supono (Jurnal Keperawatan Muhammadiyah, 2024)
Introduction: Preoperative patients with anxiety will cause an increase in breathing frequency and heart rate, potentially resulting in the cancellation of surgery. Anxious patients will be intervened through deep breath relaxation techniques that are proven to reduce anxiety levels. Method: The research design is "quasi-experimental" with a " Non-Equivalent Group Design Pre and Post Test" approach. The sampling method used was purposive sampling with a total of 20 respondents divided into two groups. Determination of respondents based on the inclusion criteria of general anesthesia patients, compositional awareness with moderate-severe APAIS anxiety levels who have scheduled surgery at Karsa Husada Batu Hospital. The independent variable is deep breath relaxation, and the dependent variable is anxiety level. Univariate analysis to determine the characteristics of respondents. Bivariate analysis using paired t-test and independent t-test to determine the difference between the two groups. Results: The paired t-test in the pre-post control group resulted in a p-value of 0.823, indicating an average increase of 0.80. Conversely, in the pre-post treatment group, the p-value was 0.000, signifying a mean decrease of 4.00. In the independent t-test between the control and treatment groups in the post-test, the p-value was 0.002. Discussion: Deep breath relaxation improves lung ventilation and blood oxygenation, involving the medulla oblongata which controls the cardiovascular and HPA which regulates the neuendocrine system. Activation of ACTH and CRH increases cortisol secretion, which is associated with anxiety.